A Study Of Cross-Cultural Consumer Values, Needs And Purchase Behavior In China And Malaysia - Bin, Wu (2005)
The research under consideration will be to examine the relationship of consumer values, needs and purchase behavior in two Asian consumer markets, namely China and Malaysia.